Expected Quality of Service (eQoS) - A Network Metric for Capturing End-User Experience - HUGGARD, MERIEL; MC GOLDRICK, CIARAN SEAMUS; PIBIRI, GIANLUIGI (IEEE, 2013)
Quality-oriented network service provisioning can take place at the network level using estimates of Intrinsic Quality of Service (IQoS) parameters or at the user level through measurements of the end-user Quality of Experience (QoE). While IQoS parameters are quantitative and measurement based, QoE estimates are more difficult to obtain as they usually rely on subjective end-user reporting. A new metric for the instantaneous estimation of QoE is proposed, expected Quality of Service (eQoS). This Perceived Quality of Service metric is calculated using IQoS parameters. eQoS estimates the QoE of common real time services for mobile devices (e.g. smartphones, tablets): Voice of IP via Constant Bit Rate, Audio and Video streaming via Variable Bit Rate. The efficiency of the proposed eQoS metric is evaluated via a realisation of an infrastructure-based wireless network. Unlike existing QoE metrics, eQoS provides an instantaneous estimate of the perceived QoS thereby establishing eQoS as an essential parameter for inclusion in future traffic management algorithms.
IEEE IFIP WIRELESS DAYS
PUBLISHED
Keywords: eQoS Quality of Service Network Metric End-User